Non-coding RNA and its network in the pathogenesis of Myasthenia Gravis - Wang, Fuqiang; Mei, Xiaoli; Yang, Yunhao; Zhang, Hanlu; Li, Zhiyang; Zhu, Lei; Deng, Senyi; Wang, Yun (Frontiers in Molecular Biosciences, 2024)
Myasthenia Gravis (MG) is a chronic autoimmune disease that primarily affects the neuromuscular junction, leading to muscle weakness in patients with this condition. Previous studies have identified several dysfunctions in thymus and peripheral blood mononuclear cells (PBMCs), such as the formation of ectopic germinal centers in the thymus and an imbalance of peripheral T helper cells and regulatory T cells, that contribute to the initiation and development of MG. Recent evidences suggest that noncoding RNA, including miRNA, lncRNA and circRNA may play a significant role in MG progression. Additionally, the network between these noncoding RNAs, such as the competing endogenous RNA regulatory network, has been found to be involved in MG progression. In this review, we summarized the roles of miRNA, lncRNA, and circRNA, highlighted their potential application as biomarkers in diagnosing MG, and discussed their potential regulatory networks in the abnormal thymus and PBMCs during MG development.